"I Am Fortunate to Have a Transgender Child": An Investigation into the Barriers and Facilitators to Support among Parents of Trans and Nonbinary Youth. Issue 1 (1st January 2022) - Matsuno, Em; McConnell, Elizabeth; Dolan, C. V.; Israel, Tania
Abstract: Research has demonstrated that parental support is a key factor in protecting trans and nonbinary youth from elevated mental health risks including depression and suicide. However, little research has investigated what barriers prevent parents from supporting their child's trans or nonbinary identity or what helps facilitate parental support. A survey of 93 parents of trans and nonbinary youth identified common barriers and facilitators to support via checklists and open-ended questions. Common barriers to support were emotional barriers such as fear of their child being bullied or hurt; lack of knowledge/skills including difficulty adjusting to a new name or pronouns; beliefs and attitudes; and systems barriers such as lack of inclusive policies at their child's school. Common facilitators to support included receiving social support from other families of trans and nonbinary youth, educational and professional resources, communicating with their child, and exposure to trans communities. Additionally, this study examined patterns in barriers and facilitators across parents categorized by level of supportiveness into three groups: supportive, somewhat supportive, and unsupportive. Implications for targeting interventions to increase parental support and future directions for research are discussed.